Using the fundamentals of programmed instruction as a teaching method on mechanical ventilation for nurses (Revista Contexto & Saúde, 2025)
Objective: To assess the effectiveness of mechanical ventilation training based on programmed instruction for nurses at a Regional University Hospital in northwest Paraná. Method: A quasi-experimental, before-and-after study, with pre- and post-intervention assessment of a single group, carried out between June and September 2022. Data was collected at three phases: pre-test, immediate post-test, and delayed post-test, the last of which took place three months after the training. The SPSS software was used for analysis, with the Friedman and Durbin-Conover Post-hoc tests. Cronbach's alpha coefficient was used to analyze the instrument. Results: In the pre-test, 51 nurses participated; in the immediate post-test, participation decreased to 45 nurses, and in the delayed post-test, 30 nurses remained involved in the study. The mean age was 42+7.56 years, 45% of the participants had double jobs, and 64% had never received training on mechanical ventilation. The pre-test had an average score of 8.73+2.21; the immediate post-test had an average score of 12.4+1.87, and the delayed post-test had an average score of 10.7+2.21. Friedman's test resulted in a p-value
Keywords: Nursing; Mechanical Ventilation; Continuing Education; Intensive Care Unit; Programmed Instruction